EFEKTIVITAS METODE UMMI DALAM MENGHAFAL AL-QUR’AN DI SEKOLAH DASAR ISLAM TERPADU AL-MUNADI MEDAN MARELAN-SUMATERA UTARA - Indi Rahmadani; Muhammad Syahminan; Sholahuddin Ashani (Jurnal Ekshis, 2025)
The Ummi method is an easy and effective method for memorizing the Qur’an that has been applied for a long time at SD IT Al-Munadi Medan. The use of the Ummi method has been running from the initial stage to significant development, and has proven effective in improving the quality of memorization of students at SD IT Al-Munadi Medan. The purpose of this study was to determine the application of the Ummi method at SD IT Al-Munadi, and to assess the quality of students’ memorization of the Qur’an at the school using the Ummi method. In addition, this study also aims to identify the advantages and disadvantages of the Ummi method at SD IT Al-Munadi Medan. The subjects in this study included several tahfidz tutors, tahfizh coordinators, principals, and several students from grades V and VI who were selected as representatives. Data collection was carried out by direct observation in the field, as well as through interviews with research subjects. In addition, documentation related to this study was also collected. The results of this study indicate that there are four mandatory levels that must be completed during education at the school, where each tahfizh group is divided based on the level of surah memorized by the students. The tahfizh tutors use various methods to support the progress and development of memorization of their tahfizh members, such as muraja’ah (repeating memorization), motivation, writing, and talaqqi (direct reading in front of the teacher). In general, the quality of students’ memorization of the Qur’an has increased significantly, although it is not achieved in a short time, but rather requires a minimum of one semester. It is hoped that in the future, this ummi method program will continue to be a means for students to memorize and improve the quality of memorization of the Qur’an, so that it can produce a generation that loves the Qur’an and makes it a guideline and guidance in life.